Impact of MMP2 rs243849 and rs14070 genetic polymorphisms on the ischemic stroke susceptibility in Chinese Shaanxi population - Li, Shilin; Yang, Shiyao; Zhang, Xiaobo; Zhang, Yu; Zhang, Jie; Zhang, Xiao; Li, Weiping; Niu, Xiaochen; Shi, Wenzhen; Zhang, Gejuan; Chang, Mingze; Tian, Ye (Frontiers in Neurology, 2022)
Background: Ischemic stroke (IS) is a complex neurological disease affected by genetics and environment. Matrix metalloproteinase-2 (MMP2) is involved in extracellular matrix (ECM) degradation, inflammation and angiogenesis to regulate the development and recovery of IS. Purposes: The aim of this study was to explore the association of rs1053605, rs243849 and rs14070 in MMP2 with the risk of IS in Chinese Shaanxi population. Methods: In this study, 677 IS patients and 681 normal controls were recruited. Rs1053605, rs243849 and rs14070 in MMP2 were genotyped. Logistic regression analysis was applied to evaluate the association of rs1053605, rs243849 and rs14070 in MMP2 with IS susceptibility and the association of environmental factors with MMP2 genetic susceptibility to IS. Results: The results of the overall analysis demonstrated that rs14070 in MMP2 significantly reduced the risk of IS in Chinese Shaanxi population (OR = 0.767, 95% CI = 0.619-0.952, P = 0.016). Subgroup analysis illustrated that rs243849 in MMP2 evidently increased the risk of IS among drinkers, while rs14070 in MMP2 apparently reduced IS susceptibility among females, participants with aged greater than 55, smokers and drinkers. Conclusions: Collectively, rs243849 and rs14070 in MMP2 were significantly associated with the risk of IS in Chinese Shaanxi population, and the dual effect of MMP2 to IS may be associated with its genetic susceptibility.